Intensity of competition in the market of greenhouse vegetables - Oleg Ivanovich Botkin; Irina Yur’evna Chazova (Экономика региона, 2012)
This paper reviews the competitive environment of the market greenhouse vegetables. Revealed specific features of the industry, determining the level of intensity of competition in the market greenhouse vegetables. Classified factors internal and external environment, identify indicators that affect the state of the market. The factors that determine the intensity of competition in the market greenhouse vegetables.The main competitors on the Russian market of greenhouse production.Identified indicators of the intensity level of competition, in particular: the level of monopolization of the market greenhouse vegetables, the level of concentration of production in the industry, the generalized index of the intensity of the competitive environment.Shows a comparative analysis of competitors’ market greenhouse vegetables in Udmurtia.Revealed competitive advantages which can help local producers to reduce the pressure of competition and intra-industry to occupy a leading position in the Russian market of greenhouse vegetable production.The dynamics of economic performance of Russian producers. Ways of improving the competitiveness of enterprises for the production of greenhouse vegetables